Effect of Foliar Application of GA3 on Morphological Features of Popular Cultivars of Apple (Malus×Domestica Borkh.) under Nursery Conditions in Mid-hill Asia - Sharma, Palak; Sharma, C. L.; Sankhyan, Neeraj; Vibhas (International Journal of Economic Plants, 2025)
The experiment was conducted during April, 2018 to February, 2019 at Dr YS Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India to study the effect of foliar applications of GA3 on nursery plants of three different cultivars of apple, viz. Gale Gala, Super Chief, and Jeromine. The experiment was laid out in Randomised Block Design (Factorial) and was replicated thrice. The growth regulators were applied at three different concentrations namely, 6.25 ppm, 12.5 ppm and 25 ppm. The growth regulators were applied to the leaves of different replications twice; once in the first week of July and the second time, a month later. The analysis of data of different treatments revealed that GA3 @ 12.5 ppm significantly increased plant growth with respect to all the growth parameters of different apple cultivars viz. plant height, stock girth, scion girth, number of leaves plant-1, leaf area, internodal length, primary root length, secondary root number, secondary root length, fresh weight of shoots, dry weight of shoots, fresh weight of roots, dry weight of roots, biomass of nursery plants, and percentage of saleable plants over control. Further, it was also observed that amongst the cultivars, Gale Gala performed noticeably better in terms of all the growth parameters namely, plant height, stock girth, scion girth, number of leaves plant-1, leaf area, internodal length, primary and secondary root length, secondary root number, fresh and dry weight of shoots and roots, biomass of nursery plants as well as percentage of saleable plants.